Comparative Study of the Removal Efficiency of Chrysopogon zizanioides (L.) and Zea mays (L.) of Copper (Cu) and Lead (Pb): Harnessing Phytoremediation Potential for Soil Recovery in a Former Dumpsite of El Salvador City, Misamis Oriental Philippines: 10.32526/ennrj/23/20250050 - Boter-Uayan, Lynnel; Lacang, Gina C. (Environment and Natural Resources Journal, 2025)
Inorganic pollutants, like heavy metals found in soil with high levels of concentration, post a serious threat to the environment. However, heavy metals such as Cu and Pb produced by waste treated with a phytoremediation technique project a positive input. An experimental-descriptive analysis was used to quantify the phytoremediation potential of vetiver grass (Chrysopogon zizanioides L.) and maize (Zea mays L.) in accumulating Cu and Pb in a former El Salvador City dumpsite, located in Misamis Oriental Philippines. The study found that the initial amounts of Cu and Pb (1,368 and 38.1 mg/kg) decreased significantly to (850 and 20.5 mg/kg) respectively. The results also showed vetiver grass exhibited concentrations of lead (of 15.12±1.20 µg/g) and copper (506.36±8.44 µg/g) in its roots. In comparison, maize concentrations were found to be: lead (10.22±5.92 µg/g) and copper (486.85±3.12 µg/g) respectively. The Translocation Factor (TF) of vetiver grass had a 0.40 value, while maize showed 0.16 and 0.17 values (for Cu and Pb). The Bioaccumulation Factor (BAF) of vetiver grass was 47.55, and for maize 32.14. The results rendered significant over the three-month study period at a 0.95 confidence level. This study concludes that vetiver grass generally accumulates higher concentrations of both lead and copper in roots and shoots compared to maize, with roots consistently showing higher metal accumulation than shoots. For future research, these results provide a foundational scientific framework for soil evaluation of dumpsite areas, and give further support to policy implementations.